Strengthening Digital Branding for Creative Economy Business Actors - Lina Susilowati; Shanti Nugroho; Munawaroh; Putri Fatmawati (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2025)
The issue of digital branding is very relevant along with the development of innovative technology. Digital branding helps creative economy business actors to interact with customers to create loyalty. This creative economy business is called "Alya Florist" located on Jl. Wahab Chasbulloh, Tambakberas, Jombang which was founded by Romi Abdul Basith. The "Alya Florist" product offers flower buckets with a variety of colors and types of flowers, which can be adjusted to certain themes or events. The problem for novice creative business actors such as "Alya Florist" is the limited knowledge about the importance of digital branding for their business. The service team carried out initial observations at "Alya Florist" related to the obstacles faced by partners. Socialization of the importance of digital branding by presenting speakers from Digital Business lecturers. The implementation stage is mentoring, 1) Instagram content creation, 2) TikTok content creation, 3) Posting "Alya Florist" flower bucket products on a Face Book account. The results of socialization and mentoring are increased knowledge and skills in digital branding and increased performance of "Alya Florist" business owners as well as increased sales turnover of flower bucket products